(untitled) (Journal of Bangladesh Institute of Planners, 2010)
Dhaka city is growing fast, which requires a growth management strategy for its orderly development in future. Urban growth rate is high and its impacts are long lasting. Dhaka is going to acquire its place in top ten cities of the world in terms of its population size in the near future that should make the people of the country proud of their capital city. But this pride cannot be pleasant because of its present state and its unplanned growth. There are fears that in the future though Dhaka may become a megalopolis, it will be full of slums or shanty-towns, short of infrastructures matching its size and status. Moreover, there would also be a maze of unplanned urbanization with its spill-over effects on all sections of the city’s population. Different parts of the city have to be brought under a well-planned system of growth with necessary reforms. The study began with the conceptualization of identifying the necessity of growth management for an orderly urban development in Dhaka. It tries to find out the causes and impacts of haphazard growth in the Wards of 43 and 46 in DCC area. It is expected that the recommendations made in this study in the form of guidelines will be useful to the relevant authorities and as well as for the developers for proper development of the study area and as well as for other similar areas of the city. Journal of Bangladesh Institute of Planners, Vol. 3, Dec 2010, pp. 113-127